Learning from Somaliland? Transferability of learning from volunteering to national health service practice in the UK. Issue 1 (December 2016) - Tillson, Esther; van Wees, Sibylle; McGowan, Charlotte; Franklin, Hannah; Jones, Helena; Bogue, Patrick; Aliabadi, Shirin; Baraitser, Paula
Abstract Background Capacity building partnerships between healthcare institutions have the potential to benefit both partners particularly in staff development. Previous research suggests that volunteering can contribute to professional development but there is little evidence on how learning is acquired, the barriers and facilitators to learning in this context or the process of translation of learning to the home environment. Results Volunteers from a healthcare partnership between the UK and Somaliland reported learning in communication, interdisciplinary working, teaching, management, leadership and service development. This learning came from observing familiar practices in unfamiliar environments; alternative solutions to familiar problems; learning about Somali culture; opportunities to assume higher levels of responsibility and new professional relationships. There was variability in the extent of translation to NHS practice. Time and support available for reflection and mentoring were important facilitators of this process. Conclusions The professional development outcomes documented in this study came directly from the experience of volunteering. Experiential learning theory suggests that this requires a complex process of critical reflection and new knowledge generation, testing and translation for use in new contexts. This process benefits from identification of learning as an important element of volunteering and support for reflection and the translation translation of learning to UK contexts. We suggest that missed opportunities for volunteer learning will remain until the volunteering process is overtly framed as part of continuing professional development.